Prevalence of Hepatitis B Infection Among Healthy Blood Donors in Rangpur, Bangladesh (Journal of Rangpur Medical College, 2023)
Background: Transfusion transmitted infection (TTIs) is still an alarming issue associated with blood transfusion, as hepatitis B remains a critical public health concern in a country like Bangladesh. The predisposition of the prevalence of HBsAg infection among healthy blood donors even in a tertiary-level hospital could be a strategy for scheming and observing this problem.Methods: A cross-sectional study was conducted among all samples of a total of 11,566 units of blood screening for hepatitis B surface antigen at Rangpur Medical College Hospital, Rangpur from January 2021 to December, 2021. The prevalence of HBV infection was measured to observe the trends. Data were collected by non-probability convenient sampling, maintaining inclusion and exclusion criteria. Face-to-face interviews, blood grouping tests, and hepatitis B surface antigen (HBsAg) screening were conducted.Results: About 66% of the blood donors were between 18 and 30 years of age, and 89.6% of them were males. All the donors were replacement donors who came voluntarily. The overall seroprevalence rate of HBV among all healthy blood donors was 1.09%. About 98.4% of HBsAg-positive blood donors were males and only 1.6% were female. Hepatitis B infection was more prevalent in the 28–36 years age group and least prevalent among those older than 48 years of age.Conclusion: The decreasing trend in the prevalence of HBV infection might be the result of improvement in donor recruitment and selection, built-up awareness, proper TTIs screening, HBV vaccination and possibly decreasing HBV infection prevalence in the general population.J Rang Med Col. March 2023; Vol. 8, No. 2:49-52